Media & entertainment law - Smartt, Ursula (Routledge, an imprint of the Taylor & Francis Group, 2020)
"Now in its fifth edition, this textbook combines comprehensive coverage with rigorous analysis of a key area of the law. The author illuminates how the courts strive to strike a balance between the freedoms and responsibilities of the press on the one hand, and an individual's right to privacy on the other. Maintaining its coverage of the law across the UK (including Scotland and Northern Ireland) and the EU, the new edition has been brought up to date with expert insights into significant developments and judgements, including: -the impact of changes in intellectual property law, data protection, GDPR and copyright law post-Brexit - including the cases of Schrems II and Ed Sheeran - analysis of new case law and developments in privacy and freedom of the media - including Duchess of Sussex (Meghan Markle) v The Mail on Sunday and ZXC v Bloomberg - the introduction of new Scottish defamation laws and the importance of defamatory meaning - the response to disinformation, fake news and social media - including tweeting jurors and contempt With a variety of pedagogical features to encourage critical thinking, this unique textbook is essential reading for media and entertainment law courses at undergraduate and postgraduate levels, and an insightful resource for students and reflective practitioners of journalism, public relations and media studies"--Provided by publisher.